New House Staff Leaders - (:unkn) unknown (Coy C. Carpenter Library, 1960)
Published in: Medical Alumni News. Spring 1960.
Newly elected officers of the House Staff Chapter of the Bowman Gray Medical Alumni Association are enjoying some "down time" in the Student Lounge in 1960. (L to R) Dr. John Nelson, Vice President, Dr. Steve Long, Secretary-Treasurer, and Dr. Robert Crouch, President.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works